Amending mine tailing cover with compost and biochar: effects on vegetation establishment and metal bioaccumulation in the Finnish subarctic - Hagner, Marleena; Uusitalo, Marja; Ruhanen, Hanna; Heiskanen, Juha; Peltola, Rainer; Tiilikkala, Kari; Hyvönen, Juha; Sarala, Pertti; Mäkitalo, Kari (Environmental Science and Pollution Research)
2021